PENGEMBANGAN MODUL ISLAMIC PARENTING BERBASIS MULTIPLE INTELLIGENCES UNTUK MENGOPTIMALISASI KECERDASAN LINGUISTIK, RUANG-VISUAL, DAN KINESTETIK BADANI ANAK - Fatkhi Fahim; Ragwan Albaar (Al-Tazkiah : Jurnal Bimbingan dan Konseling Islam, 2020)
Good parenting is one of the basic needs of children, therefore parents are obliged to provide appropriate parenting styles for children suitable for the era, so that in the end, parents could form children’s characters with good attitude and intelligence that was honed fully. Based on this, the researcher tried to develop modules that could help parents developing good parenting styles. To answer these problems, researchers used research and development methods. This research produced a product in the form of a module entitled "My Great Child". Based on the results of the pretest and posttest data analysis conducted by researchers using the Wilcoxon signed-rank test, there was zero negative rank data, there were 10 positive rank data, with no equal value before and after giving Islamic parenting material based on various intelligence. These results show that the average parenting style increase after the use of multiple intelligence-based Islamic parenting modules.